2013
DOI: 10.1007/s00216-013-7528-3
|View full text |Cite
|
Sign up to set email alerts
|

Rapid method for the measurement of circulating thyroid hormones in low volumes of teleost fish plasma by LC-ESI/MS/MS

Abstract: Thyroid hormones are critical regulators of normal development and physiological functioning in all vertebrates. Radioimmunoassay (RIA) approaches have been the method of choice for measuring circulating levels of thyroid hormones in vertebrates. While sensitive, RIA-based approaches only allow for a single analyte measurement per assay, can lack concordance across platforms and laboratories, and can be prone to analytical interferences especially when used with fish plasma. Ongoing advances in liquid chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…All analytes yielded two SRM-ion transitions; however, it was only possible to obtain a single high abundance ion-transition for T 0 and T 1 AM. Our MS/MSfragmentation is in agreement with other studies that also found similar ion fragments caused by loss of carboxylic acid for T 4 , T 3 , rT 3 [8,[21][22][23], 3,5-T 2 , and 3,3′-T 2 [16,24]. For T 1 AM, we observed a MS/MS-fragment at m/z 212, corresponding to loss of aromatic hydroxyl and iodine, which agrees with other findings [25,26].…”
Section: Lc-ms/ms Instrumentationsupporting
confidence: 95%
See 4 more Smart Citations
“…All analytes yielded two SRM-ion transitions; however, it was only possible to obtain a single high abundance ion-transition for T 0 and T 1 AM. Our MS/MSfragmentation is in agreement with other studies that also found similar ion fragments caused by loss of carboxylic acid for T 4 , T 3 , rT 3 [8,[21][22][23], 3,5-T 2 , and 3,3′-T 2 [16,24]. For T 1 AM, we observed a MS/MS-fragment at m/z 212, corresponding to loss of aromatic hydroxyl and iodine, which agrees with other findings [25,26].…”
Section: Lc-ms/ms Instrumentationsupporting
confidence: 95%
“…Washing the inside of polypropylene test tubes with methanol did not reveal any adsorbed residues. A number of protocols for extracting thyroid hormones from plasma use acids in combination with heat [8]. This prompted a more meticulous stability study to provide essential knowledge on these substances behavior ( Supplementary Fig.…”
Section: Stability Of Thyroid Hormonesmentioning
confidence: 99%
See 3 more Smart Citations